The Ethical Use of Fit Indices in Structural Equation Modeling: Recommendations for Psychologists - Stone, Bryant M. (Frontiers in Psychology, 2021)
Fit indices provide helpful information for researchers to assess the fit of their structural equation models to their data. However, like many statistics and methods, researchers can misuse fit indices, which suggest the potential for questionable research practices that might arise during the analytic and interpretative processes. In the current paper, the author highlights two critical ethical dilemmas regarding the use of fit indices, which are (1) the selective reporting of fit indices and (2) using fit indices to justify poorly-fitting models. The author highlights the dilemmas and provides potential solutions for researchers and journals to follow to reduce these questionable research practices.